Integrative DNA methylation and gene expression analysis in high-grade soft tissue sarcomas - Renner, Marcus; Wolf, Thomas; Meyer, Hannah V.; Hartmann, Wolfgang; Penzel, Roland; Ulrich, Alexis; Lehner, Burkhard; Hovestadt, Volker; Czwan, Esteban; Egerer, Gerlinde; Schmitt, Thomas; Alldinger, Ingo; et al. (Genome biology, 2013)
High-grade soft tissue sarcomas are a heterogeneous, complex group of aggressive malignant tumors showing mesenchymal differentiation. Recently, soft tissue sarcomas have increasingly been classified on the basis of underlying genetic alterations; however, the role of aberrant DNA methylation in these tumors is not well understood and, consequently, the usefulness of methylation-based classification is unclear.
Gesehen am 07.01.2022